Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4172/2476-1966.1000126
|View full text |Cite
|
Sign up to set email alerts
|

In ovo and Dietary Supplementation of Probiotics Affects Post-Hatch Expression of Immune-Related Genes in Broiler Chicks

Abstract: During the first week post-hatch, the neonatal chick is immunologically vulnerable and subject to infectious threats found in the environment. Probiotics are live, non-pathogenic microorganisms known to have a positive effect on the host by improving the natural balance of gut microbiota and promoting animal health. The objective of this study was to determine the effects of administering probiotics in ovo and in the diet on broiler chick hatchability, and post-hatch immune organ weights and ileal immune-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…Whereas, Mucin-2 gene expression was not affected in other parts of small intestinal. Pender et al (2017a), who found that in ovo inoculation of commercial probiotic at different doses (1×10 5 , 1×10 6 and 1×10 7 cfu) did not affect the expression level of Mucin-2 gene in the ileum of broilers on 4 th , 6 th , 8 th , 15 th and 22 nd day age was contrary to the present finding.…”
Section: Resultscontrasting
confidence: 99%
“…Whereas, Mucin-2 gene expression was not affected in other parts of small intestinal. Pender et al (2017a), who found that in ovo inoculation of commercial probiotic at different doses (1×10 5 , 1×10 6 and 1×10 7 cfu) did not affect the expression level of Mucin-2 gene in the ileum of broilers on 4 th , 6 th , 8 th , 15 th and 22 nd day age was contrary to the present finding.…”
Section: Resultscontrasting
confidence: 99%
“…Birds were assigned to one of the three dietary treatments (12 pens/treatment) as follows: Negative Control (NC): corn-soybean meal basal diet (Table 1); Positive control (PC): NC + 20 mg virginiamycin/kg (as 0.450 kg Stafac ® 20) diet from d 0–42; Probiotic: NC + PrimaLac (1.36 kg/ton in the starter and grower 1 diets; 0.91 kg/ton in grower 2 and finisher diets). PrimaLac contains Lactobacillus acidophilus , Lactobacillus casei , Bifidobacterium bifidum , and Enterococcus faecium [22]. All animal protocols were approved and conducted under the guidelines of the Virginia Tech Institutional Animal Care and Use Committee (IACUC # 18-011).…”
Section: Methodsmentioning
confidence: 99%
“…Average gene expression relative to GAPDH for each sample was calculated using the 2 −ΔΔCt method [24]. The calibrator for each gene was the average ΔCt value from the negative control group [22].…”
Section: Methodsmentioning
confidence: 99%